Pengaruh Ukuran Perusahaan, Capital Intensity, dan Transfer Pricing Terhadap Tax Avoidance (Studi Kasus Pada Perusahaan Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023) - Ningrum, Devi Setya; Lestari, Sri Isfantin Puji; MG Sukamdiani (JURNAL ILMIAH EDUNOMIKA, 2025)
This study examines how tax avoidance among food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2021–2023 is impacted by firm size, capital intensity, and transfer pricing. Firm size (as determined by the logarithm of total assets), capital intensity (as determined by the ratio of fixed assets to total assets), and transfer pricing (as determined by the proportion of related party receivables to total receivables) are the independent variables that are examined. The tax avoidance ratio represents the dependent variable. expense to income before tax. The study employed purposive sampling, selecting 22 companies over a three years period, resulting in 66 firm year observations. The associations between the variables were assessed using multiple linear regression. The findings show that transfer intensity significantly and favorably affects tax evasion. On the other hand, transfer pricing and firm size have little bearing.